PERLAWANAN DEPATI PARBO DI MATA KOLONIALIS BELANDA DI KERINCI: SUATU KAJIAN SEJARAH LOKAL - Johan Wahyudi (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2017)
The people war againts Dutch colonial in Kerinci is still being local thema in Indonesian history. There was some episodes, that was describing how the Dutch’s effots to reclaim the throne of Kerinci from the local kingship. One of them is Depati Parbo. For Dutch, this name is the true enemy as “trouble-maker” for seeding the Dutch’s sovereignity in the hinterland of Central Sumatra, especially in Barisan hills. In 2014, this article particiated in the historical seminar in Kerinci Jambi, that is discuccing about the Heroship of Depati Parbo on Defending Kerinci from the Dutch Treat. Before that, in searching for history of Depati Parbo is like swimming in mud. The sources of that are rare, untill I found it in ANRI (National Archive of Republic if Indonesia). I found many various colonial archives. This is the breakthrouht for facing the problem about the tiny chance in searching local historical matter. This article will explain the beginning of Dutch colonial era in Kerinci. Depati Parbo and his fighting is the door for deeping the colonial structures that ever exist in Kerinci.Keywords: local history, colonialism, local struggles and hinterland.